The development of edmodo-based learning as a means of online daily examinations at Batu Islam high school - Tikeu Yuaruan Nesitaf Sari; Mohammad Mahfud Effendi; Reni Dwi Susanti (STKIP PGRI Banjarmasin, 2019)
This study was designed to see the implementation and effectiveness of Edmodo as an online daily exam media for students. This type of research is a descriptive study with a qualitative approach. The subjects of this study were 11 students at Batu Islamic High School. The development method used in this study is the Research and Development (R&D) method using the ADDIE model. The instrument used in this study were test question and student response questionnaires. Based on research obtained by the results of Edmodo-based learning as an online test tool in Batu Islam High School can be implemented well and effectively to be developed, this is discussed with an average score of 80 students, this answer with an average value of 75.23% and the results of student responses to the use of Edmodo with an average value of 80.65%. Edmodo is an online test tool that can reduce the cheat done by compilation students taking this written test because at Edmodo there are features that are useful for practicing student discipline such as managing time.